Impact of Personal Factors on Software Quality - Guveyi, Elcin; Aktas, Mehmet S.; Kalipsiz, Oya (IEEE, 2020)
Software development is a people-oriented process. Applications designed for the solution of human problems are developed by people. While examining the quality of the software product, ignoring the individual characteristics of individuals will lead to incomplete research. This paper is a road map for the study we are conducting. We are aiming to do a comprehensive examination based on the factors examined in human factor researches in the literature. In our research, the quality metrics of the software projects to be carried out by students will be analyzed. Personal characteristics of the participants will be determined, and inferences about how much they affect the application they developed will be made.
Keywords: software quality; human factor; personality; WORK; Computer Science